Coma [videorecording (DVD)] - Crichton, Michael, 1942-2008; Bujold, Geneviève; Douglas, Michael, 1944-; Widmark, Richard; Ashley, Elizabeth, 1939-; Torn, Rip, 1931-2019-; Cook, Robin, 1940- (Warner Bros., 2000)
A young doctor at a Boston hospital becomes suspicious when healthy young people undergoing routine operations are mysteriously slipping into irreversible comas.